Synthesis method of fly ash-based nano-alumina dispersoid

By growing aluminum hydroxide nanoparticles in situ on the fly ash surface and calcining, the problem of insufficient dispersion of nano alumina in cement-based materials is solved, and efficient nano alumina dispersion and improvement of cement-based materials are achieved, avoiding the problem of particle size control in high-temperature environments and the high cost of surfactants.

CN119735388APending Publication Date: 2025-04-01SOUTHEAST UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411911938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The dispersion of nanoalumina in cement-based materials is not ideal, which limits its potential to enhance cement-based materials, and the existing methods are difficult to control the particle size of nanoalumina in high temperature environments and are costly.

Method used

Using a method without surfactant, fly ash is surface modified by a phosphoric acid solution, and alkali solution is added to an ethanol solution containing aluminum salt to grow aluminum hydroxide nanoparticles in situ, and then calcined to obtain fly ash-based nanoalumina dispersion.

Benefits of technology

The high dispersion of nano alumina on the fly ash surface is achieved, and its enhancement effect on cement-based materials is improved, and the stability problems and high costs of using surfactants are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735388A_ABST
    Figure CN119735388A_ABST
Patent Text Reader

Abstract

The invention discloses a synthesis method of a fly ash-based nano aluminum oxide dispersion, which comprises the following steps: (1) adding fly ash into a phosphoric acid solution, fully reacting, centrifuging, washing and drying to obtain fly ash with phosphoric acid functional groups grafted on the surface; (2) adding the fly ash subjected to surface modification in the step (1) into an ethanol solution containing aluminum salt, fully stirring, adding alkali liquor, fully reacting, centrifuging, washing and drying to obtain a precursor; and (3) calcining the obtained precursor to obtain the fly ash-based nano aluminum oxide dispersion. According to the synthesis method disclosed by the invention, the fly ash-based nano aluminum oxide dispersion with high dispersity can be prepared on the premise of not using a surfactant, and the dispersity of nano aluminum oxide in a cement-based material is improved by improving the dispersity of nano aluminum oxide on the surface of fly ash, so that the dispersity of the nano aluminum oxide in the cement-based material is improved. Further, the reinforcing effect of the nano aluminum oxide on the cement-based material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for synthesizing a fly ash-based nano-alumina dispersion, belonging to the technical field of nano-material preparation. Background Art

[0002] Nano-alumina has outstanding seed effect, filling effect, interface transition zone strengthening effect and extremely high volcanic ash activity. It can modify cement-based materials at the nanoscale and significantly improve the performance of cement-based materials. It has great potential for engineering applications. However, nano-alumina has a large specific surface area and high specific surface energy, and there is a significant tendency for particles to agglomerate, which results in less than ideal dispersion of nano-alumina in cement-based materials, limiting the potential of nano-alumina to enhance cement-based materials. Therefore, there are still huge challenges in achieving uniform dispersion of nano-alumina in cement-based materials.

[0003] At present, in-situ growth of nano-alumina on the surface of fly ash has become an effective method for uniform dispersion of nano-alumina in cement-based materials. However, this method has encountered great challenges in the synthesis of γ-nano-alumina and α-nano-alumina. On the one hand, γ-nano-alumina and α-nano-alumina need to be calcined at 600°C and 1000°C, respectively, but the high temperature environment will affect the stability of traditional surfactants, causing nano-alumina to agglomerate and the particle size to be difficult to control; on the other hand, the cost of surfactants is very high, which greatly increases the cost of preparing in-situ growth of nano-alumina on the surface of fly ash. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for synthesizing a fly ash-based nano-alumina dispersion. The synthesis method can prepare a fly ash-based nano-alumina dispersion with high dispersibility without using a surfactant, and improve the dispersibility of nano-alumina on the fly ash surface, thereby enhancing the reinforcing effect of nano-alumina on cement-based materials.

[0005] Technical solution: The method for synthesizing the fly ash-based nano-alumina dispersion of the present invention comprises the following steps:

[0006] (1) Fly ash is added to a phosphoric acid solution, and after sufficient reaction, the solution is centrifuged, washed, and dried to obtain fly ash with phosphoric acid functional groups grafted on the surface;

[0007] (2) adding the fly ash surface-modified in step (1) to an ethanol solution containing aluminum salt, stirring the solution sufficiently, adding alkali solution thereto, and after sufficient reaction, centrifuging, washing, and drying to obtain a precursor (in-situ precipitation of aluminum hydroxide on the surface of the fly ash);

[0008] (3) calcining the obtained precursor to obtain a fly ash-based nano-alumina dispersion.

[0009] Wherein, in step (1), the concentration of the phosphoric acid solution is 3 to 3.5 M; and the added mass ratio of fly ash to phosphoric acid is 6:5.3 to 5.5.

[0010] Wherein, in step (1), the termination condition of the centrifugation and washing is that the pH value of the obtained surface-modified fly ash is not less than 6.5, which means that all the unreacted acid has been removed.

[0011] Wherein, in step (1), the drying temperature is 80-90°C, and the drying time is 68-72 hours; in step (2), the drying temperature is 100-120°C, and the drying time is 1.5-2 hours.

[0012] Wherein, in step (2), the aluminum salt is one of aluminum chloride, aluminum sulfate or aluminum nitrate; and in the solution, the concentration of the aluminum salt is 0.5 to 0.6 M.

[0013] Wherein, in step (2), the mass ratio of the aluminum salt to the surface-modified fly ash is 4 to 5:3.

[0014] Wherein, in step (2), the alkali solution is an ethanol solution of aqueous ammonia, and the concentration of aqueous ammonia in the solution is 0.2-0.3M.

[0015] Wherein, the mass ratio of the ammonia water to the surface-modified fly ash is 0.7-0.9:9.

[0016] Wherein, in step (2), the addition rate of the alkali solution is 15 to 20 mL / min, and the reaction rate is controlled to obtain nanoparticles with uniform particle size; and the reaction time is 55 to 60 min.

[0017] Wherein, in step (3), the calcination temperature is 600-1000° C., and the calcination time is 1.5-2 hours.

[0018] Principle of the invention: First, the original fly ash is surface modified using a phosphoric acid aqueous solution, which can not only remove impurities in the original fly ash, but also induce phosphoric acid functional groups on its surface; these functional groups are connected to the fly ash through strong bonds and show electronegativity, which can generate electrostatic repulsion with negatively charged nano-aluminum hydroxide. Then, the surface modified fly ash is added to the ethanol solution of AlCl3, and the surface modified fly ash is evenly distributed in the solution. When the ammonia ethanol solution is added, Al(OH)3 precipitation grows in situ on the surface modified fly ash at the bottom of the reactor. In this process, the positively charged surface modified fly ash attracts Al(OH)3 nanoparticles to its surface by electrostatic attraction, and the phosphate functional group exerts a repulsive force on the in situ grown Al(OH)3 (the phosphate groups all show electronegativity, and the aluminum hydroxide nanoparticles with multiple hydroxy groups on the surface also show electronegativity, while the fly ash particle matrix is ​​positively charged; thus, the negatively charged aluminum hydroxide particles are attracted to the fly ash surface for nucleation and growth, and the evenly distributed phosphate groups exert a repulsive force on the nano aluminum hydroxide particles, thereby ensuring that the aluminum hydroxide nanoparticles on the fly ash surface are dispersed with each other), thereby achieving excellent dispersion of Al(OH)3 on the fly ash surface. Al(OH)3@fly ash is centrifuged, washed and calcined to obtain in-situ grown γ-nano-alumina and α-nano-alumina; similar to Al(OH)3@fly ash, the stability of the phosphoric acid functional group ensures the high dispersion of γ-nano-alumina and α-nano-alumina on the fly ash surface. The specific reaction process is as follows:

[0019] AlCl3·6H2O+3NH4OH→Al(OH)3↓+3NH4Cl+6H2O

[0020]

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: the synthesis method of the present invention can prepare a fly ash-based nano-alumina dispersion with high dispersibility without using a surfactant. The present invention improves the dispersibility of nano-alumina on the fly ash surface, thereby improving the dispersibility of nano-alumina in cement-based materials, thereby improving the reinforcing effect of nano-alumina on cement-based materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the SEM morphology of Syn-Al(OH)3 obtained in Example 1;

[0023] Figure 2 This is the SEM morphology of I-Al(OH)3@MFA obtained in Example 2;

[0024] Figure 3 This is the SEM morphology of I-γ-Al2O3@MFA obtained in Example 2;

[0025] Figure 4 This is the SEM morphology of I-α-Al2O3@MFA obtained in Example 2;

[0026] Figure 5 This is the SEM morphology of I-Al(OH)3@MFA prepared using surfactant;

[0027] Figure 6 XRD diffraction patterns of MFA, I-γ-Al2O3@MFA and I-α-Al2O3@MFA obtained in Example 2;

[0028] Figure 7 TG curves of Syn-Al(OH)3, I-Al(OH)3@MFA and MFA obtained in Example 1 and Example 2;

[0029] Figure 8 Schematic diagram of the growth and adsorption mechanism of in-situ grown nanoparticles of the present invention. DETAILED DESCRIPTION

[0030] Example 1

[0031] (1) 12 g of AlCl3·6H2O was dispersed in 100 mL of ethanol to prepare a 0.5 M AlCl3·6H2O ethanol solution in a reaction bottle, which was placed on a magnetic stirrer and stirred at a constant speed of 600 rpm for 5 minutes to prepare solution A; 0.7 g of ammonia water was dissolved in 100 g of ethanol to prepare a 0.2 M ammonia water ethanol solution in a reaction bottle, which was placed on a magnetic stirrer and stirred at a constant speed of 600 rpm for 5 minutes to prepare solution B;

[0032] (2) Solution B was added to solution A at a rate of 15 mL / min. The mixture was stirred continuously at 600 rpm for 60 minutes, and a white Syn-Al(OH)3 precipitate was formed at the bottom of the reaction vessel. The entire synthesis process was carried out at room temperature, and the deionized water was centrifuged and washed to separate the liquid and solid phases. The rotation speed was 12000 rpm and the separation time was 20 minutes. The mass ratio of Syn-Al(OH)3 to deionized water was maintained at 3:1. The centrifugation and washing steps were repeated 3 times. Finally, the Syn-Al(OH)3 was dried in an oven at 100°C for 2 hours.

[0033] Figure 1 This is the SEM morphology of Syn-Al(OH)3 obtained in Example 1. Figure 1 The average particle size of Syn-Al(OH)3 is 44.8nm.

[0034] Example 2

[0035] The method for synthesizing the fly ash-based nano-alumina dispersion of the present invention comprises the following steps:

[0036] (1) 265 g of phosphoric acid was dissolved in 900 g of deionized water to prepare a 3 M phosphoric acid aqueous solution; 300 g of O-FA (original fly ash) was added to the phosphoric acid aqueous solution, and the mass ratio of O-FA to deionized water in the acid solution was 1:3; the mixture was stirred at 600 rpm for 6 hours at room temperature; finally, the liquid solid phase was separated by centrifugal washing at 4200 rpm, and the solid was repeatedly centrifuged and washed 8 times with deionized water, and the obtained product was MFA (surface modified fly ash); during the centrifugal washing, the mass ratio of deionized water to MFA was maintained at 4:1, and the washing step was repeated eight times to make the pH of the MFA washing solution become ≈6.5; the obtained MFA sample was dried in an oven at 80°C for 3 days to achieve complete surface drying;

[0037] (2) Disperse 12 g of AlCl3·6H2O in 100 mL of ethanol to prepare a 0.5 M AlCl3·6H2O ethanol solution in a reaction flask, place it on a magnetic stirrer, and stir it at a constant speed of 600 rpm for 5 minutes; dissolve 0.7 g of ammonia water in 100 g of ethanol to prepare a 0.2 M ammonia water ethanol solution in a reaction flask, place it on a magnetic stirrer, and stir it at a constant speed of 600 rpm for 5 minutes;

[0038] (3) Add 9 g of MFA from step (1) to an ethanol solution of AlCl3·6H2O, stir at 600 rpm, and mix for 10 minutes to obtain a suspension; pump an ethanol solution of ammonia into the suspension A at a constant feed rate of 15 mL / min, and react at a speed of 600 rpm for 1 hour at an average room temperature of 22±3°C; after the reaction, in situ grow Al(OH)3 on MFA, i.e., I-Al(OH)3@MFA; centrifuge at 4200 rpm, and then wash with deionized water; repeat the centrifugation and washing steps three times, and during the washing process, maintain the mass ratio of I-Al(OH)3@MFA to deionized water at 3:1; finally, dry the I-Al(OH)3@MFA in an oven at 100°C for 2 hours to obtain a precursor;

[0039] (4) calcining the precursor obtained in step (3) at 600°C for 2 hours to obtain I-γ-Al2O3@MFA (γ-INA@MFA); or calcining the precursor obtained in step (3) at 1000°C for 2 hours to generate I-α-Al2O3@MFA (α-INA@MFA).

[0040] Figure 2 This is the SEM morphology of I-Al(OH)3@MFA obtained in Example 2. Figure 2It can be seen that the Al(OH)3 nanoparticles grown in situ on MFA are evenly distributed without large agglomerates, indicating that Al(OH)3 has good dispersion when grown in situ on MFA, indicating that I-Al(OH)3@MFA has excellent dispersion on fly ash due to the presence of phosphoric acid functional groups on MFA because the surface of MFA is modified by phosphoric acid; the average particle size of Al(OH)3 on MFA is 48.6nm.

[0041] Figure 3 This is the SEM morphology of I-γ-Al2O3@MFA obtained in Example 2. Figure 3 It can be seen that γ-INA (γ-INA or α-INA refers to two different crystal forms of in-situ grown nano-alumina, only refers to alumina nanoparticles; I-γ-Al2O3@MFA or I-α-Al2O3@MFA refers to fly ash-based in-situ grown nano-alumina (α or γ crystal form), including alumina nanoparticles and fly ash matrix) has excellent dispersibility after calcination like I-Al(OH)3@MFA. The average particle size of γ-INA is 25.1nm. The size of I-Al(OH)3 in γ-INA is reduced from 48.6nm to 25.1nm, which is due to the dehydration of I-Al(OH)3 during the calcination process at 600℃ to form γ-INA.

[0042] Figure 4 This is the SEM morphology of I-α-Al2O3@MFA obtained in Example 2. Figure 4 It can be seen that α-INA has excellent dispersibility after calcination, just like I-Al(OH)3@MFA. The average particle size of α-INA is 26.3nm. The good dispersibility of α-INA indicates that during the formation of α-INA, the phosphoric acid functional group on MFA has high stability even at 1000°C. Therefore, the synthesis method of the present invention can achieve good dispersibility of α-INA on the fly ash surface without any surfactant.

[0043] Figure 5 This is the SEM morphology of I-Al(OH)3@MFA prepared by using surfactant in the prior art. Figure 5 It can be seen that the dispersion of I-Al(OH)3 nanoparticles on the surface of I-Al(OH)3@MFA prepared by using surfactant is poor, the spacing between nanoparticles is different, and there are several nanoparticle agglomerates in the field of view. Figure 2 ), which shows that the in-situ grown nanoparticles prepared by the method of the present invention have better dispersibility on fly ash.

[0044] Figure 6XRD diffraction patterns of MFA, I-γ-Al2O3@MFA and I-α-Al2O3@MFA obtained in Example 2. The characteristic peaks of γ-NA and α-NA in γ-INA and α-INA are shown, indicating that γ-INA and α-INA have been successfully encapsulated on the surface of MFA.

[0045] Figure 7 TG curves of Syn-Al(OH)3, I-γ-Al2O3@MFA and I-α-Al2O3@MFA obtained in Example 1 and Example 2. It is calculated that the amount of γ-INA and α-INA grown on the surface of MFA is 32.3% of the mass of I-γ-Al2O3@MFA or I-α-Al2O3@MFA.

[0046] The γ-INA and α-INA obtained in Example 2 were used to prepare cement slurry samples, and their fluidity and compressive strength were tested. The preparation process was operated with reference to the slurry molding method and flow test method described in the national standard GB / T 8077-2012 "Test method for homogeneity of concrete admixtures". The proportion of nanomaterials to cement in the slurry sample was 0.5wt%, and the corresponding amount of γ-INA@MFA and α-INA@MFA was calculated based on the mass concentration of γ-INA and α-INA in γ-INA@MFA and α-INA@MFA being 32.3%. Commercial γ-NA and α-NA (abbreviated as γ-CNA and α-CAN, α-CAN and γ-CNA refer to two commercial nano alumina with different crystal forms) with the same particle size as γ-INA and α-INA were also used in the same proportion and compared. The prepared slurry was cast into a 160×40×40cm 3 The cement paste ratio is shown in Table 1; the fluidity and compressive strength test results of each cement paste sample in Table 1 are shown in Table 2.

[0047] Table 1 shows the mix ratio of cement paste

[0048]

[0049] Table 2 shows the test results of fluidity and compressive strength of each cement paste sample

[0050]

[0051]

[0052] The experimental results in Table 2 show that the cement paste fluidity of γ-INA and α-INA is significantly enhanced compared with γ-CNA and α-CNA. This trend is reflected in the compressive strength test of cement paste. At 7 days, the compressive strength of cement samples of γ-CNA and α-CNA decreased compared with the Ref sample due to the severe agglomeration tendency. In contrast, cement samples of γ-INA and α-INA showed continuous strength improvement at 7 days and 14 days, and γ-INA performed better due to its amorphous nature and superior dispersion. Although the compressive strength of α-INA was slightly lower after 7 days compared with the Ref sample, its performance still exceeded that of α-CNA due to its reduced agglomeration and enhanced dispersion. The difference in fluidity and compressive strength results confirmed that the in-situ grown nanoparticles showed excellent dispersion in cement-based composites. This improved dispersion reduced water inclusions, lowered water demand, and significantly improved cement performance.

[0053] Figure 8 The schematic diagram of the nanoparticle growth and adsorption mechanism of the in-situ growth method of the present invention is shown in FIG. Aluminum salt is hydrolyzed into electronegative polyhydroxy Al(OH)3 monomer ( Figure 8 a), these monomers are attracted to the surface of fly ash particles with positive charges and begin to nucleate and gradually grow into Al(OH)3 nanoparticles ( Figure 8 b). When the nanoparticles grow to a certain size, due to the presence of evenly distributed electronegative phosphate functional groups on the surface of the fly ash treated with phosphoric acid, these phosphate functional groups generate electrostatic repulsion with the Al(OH)3 nanoparticles, preventing the nanoparticles from continuing to grow and agglomerating with each other, thereby obtaining I-Al(OH)3@MFA ( Figure 8 c). I-Al(OH)3@MFA was converted into I-γ-Al2O3@MFA after calcination at 600℃ ( Figure 8 d), in this process, the diameter of the nanoparticles will be slightly reduced due to the dehydration of Al(OH)3 to form γ-Al2O3; after further heating to 1000℃ and calcination, it will be converted into I-α-Al2O3@MFA ( Figure 8 e), in this process, only the crystal form transformation occurs, and the diameter of the nanoparticles does not change.

Claims

1. A method for synthesizing fly ash-based nano-alumina dispersion, characterized in that: The steps include: (1) Fly ash is added to a phosphoric acid solution, and after sufficient reaction, the solution is centrifuged, washed, and dried to obtain fly ash with phosphoric acid functional groups grafted on the surface; (2) adding the fly ash surface-modified in step (1) to an ethanol solution containing aluminum salt, stirring the solution sufficiently, adding alkali solution thereto, and after sufficient reaction, centrifuging, washing, and drying to obtain a precursor; (3) calcining the obtained precursor to obtain a fly ash-based nano-alumina dispersion.

2. The synthesis method according to claim 1, characterized in that: In step (1), the concentration of the phosphoric acid solution is 3-3.5M; the mass ratio of the fly ash to the phosphoric acid is 6:5.3-5.

5.

3. The synthesis method according to claim 1, characterized in that: In step (1), the end condition of the centrifugation and washing is that the pH value of the obtained surface modified fly ash is not less than 6.

5.

4. The synthesis method according to claim 1, characterized in that: In step (1), the drying temperature is 80-90° C., and the drying time is 68-72 hours; in step (2), the drying temperature is 100-120° C., and the drying time is 1.5-2 hours.

5. The synthesis method according to claim 1, characterized in that: In step (2), the aluminum salt is one of aluminum chloride, aluminum sulfate or aluminum nitrate; and the concentration of the aluminum salt in the solution is 0.5 to 0.6 M.

6. The synthesis method according to claim 1, characterized in that: In step (2), the mass ratio of the aluminum salt to the surface-modified fly ash is 4 to 5:

3.

7. The synthesis method according to claim 1, characterized in that: In step (2), the alkali solution is an ethanol solution of aqueous ammonia, and the concentration of aqueous ammonia in the solution is 0.2-0.3M.

8. The synthesis method according to claim 7, characterized in that: The mass ratio of the ammonia water to the surface-modified fly ash is 0.7-0.9:

9.

9. The synthesis method according to claim 1, characterized in that: In step (2), the addition rate of the alkali solution is 15-20 mL / min, and the reaction time is 55-60 min.

10. The synthesis method according to claim 1, characterized in that: In step (3), the calcination temperature is 600-1000° C., and the calcination time is 1.5-2 hours.

Citation Information

Patent Citations

  • Method for preparing oil-soluble aluminum hydroxyl nano particle by in-situ surface modification

    CN101240123A

  • Preparation method of carbon nanotube reinforced alumina-based composite material

    CN109081684A

  • Method for preparing anti-hard agglomerated nano alumina particles

    CN109534378A